2020
DOI: 10.3390/cancers13010022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-Dose Irradiation of the Lung and Heart on Toxicity and Pulmonary Function Parameters after Thoracic Radiotherapy

Abstract: Objective: To assess the impact of (low) dose irradiation to the lungs and heart on the incidence of pneumonitis and pulmonary function changes after thoracic radiotherapy (RT). Methods/Material: Data of 62 patients treated with curative thoracic radiotherapy were analyzed. Toxicity data and pulmonary function tests (PFTs) were obtained before RT and at 6 weeks, at 12 weeks, and at 6 months after RT. PFTs included ventilation (e.g., vital capacity) and diffusion parameters (e.g., diffusion capacity for carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In the OAR lung, it is of utmost importance to minimise radiation exposure as the tissue is highly sensitive to radiation (Marks et al 2010;Oertel et al 2021 Jun 12). However, several clinical studies, including this one, have shown that lung sparing with HT is feasible (Wilhelm-Buchstab et al 2020;Schröder et al 2020;. In our patient cohort, none had acute (< 6 months) severe radiationinduced lung injury, suggesting a beneficial effect of lung dose reduction, despite the fact that certain chemotherapeutic agents, such as fludarabine-containing regimens, are impacting on pulmonary outcome (Oertel et al 2021).…”
Section: Discussionmentioning
confidence: 65%
“…In the OAR lung, it is of utmost importance to minimise radiation exposure as the tissue is highly sensitive to radiation (Marks et al 2010;Oertel et al 2021 Jun 12). However, several clinical studies, including this one, have shown that lung sparing with HT is feasible (Wilhelm-Buchstab et al 2020;Schröder et al 2020;. In our patient cohort, none had acute (< 6 months) severe radiationinduced lung injury, suggesting a beneficial effect of lung dose reduction, despite the fact that certain chemotherapeutic agents, such as fludarabine-containing regimens, are impacting on pulmonary outcome (Oertel et al 2021).…”
Section: Discussionmentioning
confidence: 65%
“…The need for dose reduction in patients receiving 4 Gy is questionable given that this dose may have minor toxic effects [ 19 ]. That is, a marginal reduction in lung tissue toxicity may not warrant the additional time needed to plan for lung sparing.…”
Section: Discussionmentioning
confidence: 99%
“…This exposure can have long-term effects on the lungs 13 , including a slight increase in the risk of lung cancer, fibrosis (scarring of the lung tissue) and impaired lung function. Studies have shown that exposure to low doses, can lead to changes in the DNA of lung cells that can result in mutations and an increased risk of lung cancer.…”
Section: B Vmat and Low Doses (<10gy)mentioning
confidence: 99%